A 10-year systematic review on the incorporation of digital games for multimodal literacy education - Shen, Yanan; Ab Jalil, Habibah; Jamaluddin, Rahimah (World Scientific and Engineering Academy and Society, 2024)
-Digital games increasingly penetrate young people’s lives and have become a prominent tool for 21st-century teaching and learning. While digital games are promising resources for fostering multimodal literacy, empirical evidence of their application in educational settings remains limited. This study conducted a 10-year systematic review of 20 relevant empirical journal articles to provide a comprehensive understanding of utilizing digital games in multimodal literacy learning across primary, secondary, and higher education levels. The findings revealed the main contextual features, game features, theoretical and methodological perspectives, and the possibilities of digital games for multimodal literacy learning. In conclusion, the extant empirical studies prove that digital games are legitimate learning resources to foster students’ multimodal literacy, whereas limitations are also evident. Correspondingly, this study provided recommendations to address these limitations and leverage digital games for 21st-century literacy education, thus contributing to computer research in educational contexts.